Rate and Predictors of Failure in the Conservative Management of Stable Thoracolumbar Burst Fractures: A Systematic Review and Meta-Analysis. Issue 6 (July 2022) - Tan, Terence; Huang, Milly S.; Rutges, Joost; Marion, Travis E.; Fitzgerald, Mark; Hunn, Martin K.; Tee, Jin
Study Design: Systematic review. Objectives: Management of stable traumatic thoracolumbar burst fractures in neurologically-intact patients remains controversial. Conservative management fails in a subset of patients who require subsequent surgical fixation. The aim of this review is to (1) determine the rate of conservative management failure, and (2) analyze predictive factors at admission influencing conservative management failure. Methods: A systematic review adhering to PRISMA guidelines was performed. Studies with data pertaining to traumatic thoracolumbar burst fractures without posterior osteoligamentous injury (e.g. AO Type A3/A4) and/or the rate and predictive factors of conservative management failure were included. Risk of bias appraisal was performed. Pooled analysis of rates of failure was performed with qualitative analysis of predictors of conservative management failure. Results: 16 articles were included in this review (11 pertaining to rate of conservative management failure, 5 pertaining to predictive risk factors). Rate of failure of conservative management from a pooled analysis of 601 patients is 9.2% (95% CI: 4.5%-13.9%). Admission factors predictive of conservative management failure include age, greater initial kyphotic angle, greater initial interpedicular distance, smaller initial residual canal size, greater Load Sharing Classification (LSC) score and greater admission Visual Analog Scale (VAS) pain scores. Conclusion: A proportion (9.2%) of conservatively managed, neurologically-intact thoracolumbar burst fractures fail conservative management. Among other factors, age, kyphotic angle, residual canal area and interpedicular distance should be investigated in prospective studies to identify the subset of patients prone to failure of conservative management. Surgical management should be carefully considered in patients with the above risk factors.